Eye Movement in Unipolar and Bipolar Depression: A Systematic Review of the Literature - Carvalho, Nicolas; Laurent, Eric; Noiret, Nicolas; Chopard, Gilles; Haffen, Emmanuel; Bennabi, Djamila; Vandel, Pierre (Frontiers in Psychology, 2015)
Background: The analysis of eye movements (EM) by eye-tracking has been carried out for several decades to investigate mood regulation, emotional information processing, and psychomotor disturbances in depressive disorders. Method: A systematic review of all English language PubMed articles using the terms “saccadic eye movements” OR “eye-tracking” AND “depression” OR “bipolar disorders” was conducted using PRISMA guidelines. The aim of this review was to characterize the specific alterations of EM in unipolar and bipolar depression. Results: Findings regarding psychomotor disturbance showed an increase in reaction time in prosaccade and antisaccade tasks in both unipolar and bipolar disorders. In both disorders, patients have been reported to have an attraction for negative emotions, especially for negative pictures in unipolar and threatening images in bipolar disorder. However, the pattern could change with aging, elderly unipolar patients disengaging key features of sad and neutral stimuli. Methodological limitations generally include small sample sizes with mixed unipolar and bipolar depressed patients. Conclusion: Eye movement analysis can be used to discriminate patients with depressive disorders from controls, as well as patients with bipolar disorder from patients with unipolar depression. General knowledge concerning psychomotor alterations and affective regulation strategies associated with each disorder can also be gained thanks to the analysis. Future directions for research on eye movement and depression are proposed in this review.